(untitled) (Proceedings of the International Conference on Public Health, 2017)
Lead is the heavy metals that pollute the air and lead exposure continues to be the most serious public health problem. Increased lead absorption causes negative effect such us increased number of basophilic stippling erythrocytes. Battery smelting industry is an important source of lead pollutants today. Cinangka is one village in Bogor District that has battery smelting. Based on the results of investigation by KPBB (Komite Penghapusan Bensin Bertimbal) in 2010, the mean of blood lead levels (BLL) in Cinangka children’s was 36.6 µg/dl (WHO threshold = 10 ug/dl).Aim of this study was to analyze the effects of BLL on the basophilic stippling erythrocytes in children. This study used a cross-sectional design. Blood samples were taken from 103 children in Cinangka Village Bogor District, Indonesia (2014) to measure BLL and basophilic stippling erythrocytes. A questionnaire used to determine the data on the level of parent’s education, parent’s income and nutrient intake. A nutritional status was known by calculating the Body Mass Index. Overall, 103 children (43 boys and 60 girls) with mean±SD age of 11,27±1,03 years were studied. The mean BLL on children was 14,70 µg/dl, whereas the lowest BLL 0,05 µg/dl and the highest BLL 52,11 µg/dl. The results also showed 61.2% of children had high BLL (≥ 10 µg/dl). Statistical analysis with chi square showed that the BLL (p = 0.001) and mother’s education level (p = 0.005) had significant association with basophilic stippling. Based on multivariate anaylisis, BLL was the most dominant variables associated with basophilic stippling.